Assessment of Human Urine and Sputum Samples for Multiple Antibiotic Resistance Patterns and Genomic DNA Analysis of Escherichia coli - Mehbuba, Gazi; Barman, Ashok Kumar; Marma, Meshing; Iqbal, Evana (Bangladesh Journal of Infectious Diseases, 2025)
Background: Antimicrobial resistance (AMR) surveillance is inadequate in low-and middle-income countries, and first-choice antibiotic therapy recommendations need to be confirmed by precise data on antibiotic susceptibility. Objective: This study was about isolating and identifying Escherichia coli (E. coli) from human urine and sputum samples and evaluating the antibiotic sensitivity pattern. Methodology: This retrospective study investigated antimicrobial resistance (AMR) in E. coli isolated from 200 human urine and sputum samples collected from patients who showed symptoms of urinary tract infections at Kurmitola General Hospital, Dhaka, Bangladesh, during February and March 2019. The samples were selectively screened to assess their antibiograms and plasmid profiles. Laboratory analysis was performed using staining techniques, culture methods, and biochemical characterization, followed by polymerase chain reaction (PCR). The antibiotic susceptibility of the isolates was determined using the disc diffusion method." Results: We have screened 25 urine and sputum samples for antibiotic resistance. Here about six selective E. coli from Urine and two sputum samples were discussed for further Plasmid DNA analysis. The antibiotics sensitivity patterns and plasmid profiling were done to find out the possible correlation between plasmids and antibiotic sensitivity patterns of Escherichia coli isolates. Antibiogram study revealed that imipenem 12.0%, meropenem 3.0%, ciprofloxacin 7.0%, norfloxacin 7.0%, levofloxacin 12.0%, amoxicillin 11.0%, chloramphenicol 1.0%, gentamicin 6.0%, kanamycin 9.0%, cefuroxime 11.0%, erythromycin 7%, vancomycin 7.0%, tetracycline 7% resistance. Out of the eight isolates tested, 25.0% showed the presence of plasmid and 55.0% of E. coli isolates positive for different primers. NDM (24.0%) has shown maximum gene expression. SHV (4.0%), and BlaTEM (4.0%) showed minimum gene expression out of the eight primers. Conclusion: Escherichia coli isolates from different samples have increased antimicrobial resistance, particularly to levofloxacin, imipenem, amoxicillin, cefuroxime and kanamycin. Bangladesh Journal of Infectious Diseases, December 2024;11(2):121-130